RETRACTED: The integrative communicative technologies as a factor in the formation of ecological culture and eco-friendly communication of students - Chernitsynа Margarita M.; Kolmikova Viktoria А. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001